Discounting and sustainability: towards reconciliation. (12th May 2004) - Howarth, Richard B.
This paper examines the well-known tension between discounting and sustainability in the long-term management of environmental resources. The paper describes a rights-based ethical framework in which present decision-makers hold a moral duty to ensure that life opportunities are sustained from generation to generation. Maintaining opportunities requires that natural resources must be either conserved or replaced with proven substitutes that provide equivalent services. In this framework, discounting procedures are useful in characterising decision-makers' preferences concerning tradeoffs between costs and benefits that arise at different points in time. Such preferences, however, are trumped by duties to posterity in cases where discounting favours the uncompensated depletion of resource stocks.